Analisis Perhitungan Dan Penyetoran PPh Pasal 23 Atas Jasa Sewa Pada PT. Perkebunan Nusantara VI - Johandri Iqbal; Heriyani Heriyani; Habiba Oktarina (LPPM Politeknik Jambi, 2022)
Article 23 income tax is a mandatory contribution to the state owed by an individual or entity that is coercive in nature based on the law, without receiving direct compensation and being used for the state's purposes for the greatest prosperity of the people. The purpose of this study was to find out how the calculation and deposit of Article 23 Income Tax for rental services at PT. Perkebunan Nusantara VI Jambi is in accordance with the Law of the Minister of Finance Regulation No. 141/PMK.03/2015. The analytical method used in this study is the quantitative descriptive method, namely the method by collecting data, compiling and then interpreting and analyzing it by reprocessing the data obtained so as to provide complete information. In this study, the calculation and collection of Article 23 Income Tax on rental services at PT. Perkebunan Nusantara VI Jambi has complied with the Regulation of the Minister of Finance No. 141/PMK.03/2015 which is subject to a tax of 2% of the tax base excluding PPh 21.